Incidence and Time Trends of Type 2 Diabetes Mellitus among Adults in Zhejiang Province, China, 2007-2017 - Meng Wang; Wei-Wei Gong; Jin Pan; Fang-Rong Fei; Hao Wang; Min Yu; Xiao-Yan Zhou; Ru-Ying Hu (Journal of Diabetes Research)
Aims. Population-based incidence data are paramount to assess the effects of prevention strategies for diabetes, yet the relevant studies in mainland China are scarce. This study is aimed at estimating the type 2 diabetes mellitus (T2DM) incidence and time trends in Chinese adults. Material and Methods. Based on the Diabetes Surveillance System of Zhejiang Province, 879,769 newly diagnosed T2DM cases were identified from January 1, 2007, to December 31, 2017. Annual incidence, incidence rate ratios (IRRs), and average annual percentage change with their 95% confidence intervals (CIs) were reported. Results. The age-standardized overall incidence rate of T2DM was reported to be 281.73 (95% CI: 281.26-282.20) per 100,000 person-years, 293.19 (95% CI: 292.51-293.87) in males and 270.42 (95% CI: 269.76-271.09) in females. Compared with the ≥80 years age group, younger adults were at lower risk for T2DM (IRRs ranged from 0.035 to 0.986 and the 95% CIs did not include the null), except for the 70-79 years age group (IRR: 1.087, 95% CI: 1.077-1.097). Compared with females and rural areas, the risk for T2DM was higher in males (IRR: 1.083, 95% CI: 1.079-1.088) and urban areas (IRR: 1.005, 95% CI: 1.001-1.009), respectively. The standardized annual incidence rate increased from 164.85 in 2007 to 268.65 per 100,000 person-years in 2017, with an average annual increase of 4.01% and grew more rapidly in male, younger, and rural area populations. Conclusions. Our study suggested a significant increase in the incidence rate of T2DM among Chinese over the past decade, especially in adults characterized by male sex, younger age, and rural areas.